اسلامی تہذیب کی نشاۃ ثانیہ کے عصری محرکات: فکری و نظریاتی تجزیہ: Contemporary Motivations for the Renaissance of Islamic Civilization: An Intellectual and Ideological Analysis - Dr. Muhammad Riaz Mahmood; Dr. Muhammad Irfan Ahmad (International Research Journal of Arabic and Islamic Studies, 2024)
This article presents an analysis of contemporary motivations for the renaissance of Islamic civilization. The qualitative research methodology has been utilized for this purpose. Islamic civilization has shown extraordinary performance in the religious, cultural, moral and social fields in the service of humanity. As a result of the individual and collective weaknesses of the Muslims, this civilization has now faded into the background. Many Muslims are the bearers of the renaissance of this civilization due to the awakening of the consciousness of civilizational identity and the study of the world situation. There are many religious, political and social motivations for this intellectual dynamism and ideological struggle. The study of these contemporary motivations is an important need of the academic circles. This article has been presented for the fulfilment of this academic and research need.